Advances in clinical chemistry. - Makowski, Gregory (Academic, 2009)
Volume 48 in the internationally acclaimed Advances in Clinical Chemistry contains chapters submitted from leading experts from academia and clinical laboratory science. Authors are from a diverse field of clinical chemistry disciplines and diagnostics ranging from basic biochemical exploration to cutting-edge microarray technology. * Leading experts from academia and clinical laboratory science * Volume emphasizes novel laboratory advances with application to clinical laboratory diagnostics and practical basic science studies.